Pediatric Transepiphyseal Seperation and Dislocation of the Femoral Head - Mehmet Elmadag; Hasan H. Ceylan; Ahmet Can Erdem; Kerem Bilsel; Gokcer Uzer; Mehmet Ali Acar (Case Reports in Orthopedics)
Pediatric hip fractures and dislocations are rare in practice and are related to high-energy trauma. The incidence of postoperative avascular necrosis is increasing, especially in the case of transepiphyseal fractures. Surgery is the most common form of treatment, and its timing is important for prognosis of the fracture. Patients and their families should be informed about the possibility of avascular necrosis and further complications related to the fracture.